If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3a + 2) = 52 Reorder the terms: -4(2 + 3a) = 52 (2 * -4 + 3a * -4) = 52 (-8 + -12a) = 52 Solving -8 + -12a = 52 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -12a = 52 + 8 Combine like terms: -8 + 8 = 0 0 + -12a = 52 + 8 -12a = 52 + 8 Combine like terms: 52 + 8 = 60 -12a = 60 Divide each side by '-12'. a = -5 Simplifying a = -5
| 48400=(2x+2)(x) | | y=25x^2+10x-24 | | 8.4+b=-22.9 | | -3(x-4)+7x=8x+-8 | | 12+2l+2w=12 | | 4(2a+1)=60 | | 3X+2Y=34 | | 61=4+q | | 7x^2+28x+196=0 | | -5(t-1)+t=5t-9 | | 5x^2+45x+70= | | x*2-6x-4=0 | | X(2x-5)+(3x+4)(6x-1)= | | 3x^2+42x+441=0 | | 73x-15=48+99 | | x+(x*.04)=2.75 | | (x+0.2)(x+3.9)=0 | | 28d+1=28 | | x^2+4x+28=0 | | x+x(.04)=2.75 | | 3(7-2h)=9 | | x^2=y-1 | | -s+3=52+21 | | x^2+34x+2= | | -x^2+565x-8250=0 | | (x-y)(x^2-10xy+y^2)=0 | | b-[x+4a+(x-7)]= | | 9+4+4v-2v+6=11 | | 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) |